Investment and CEO compensation under limited commitment - Ai, Hengjie; Li, Rui (Journal of Financial Economics, 2015)
We extend the neoclassical investment model (Hayashi, 1982) to allow for limited commitment on compensation contracts. We consider three types of limited commitment: (i) managers cannot commit to compensation contracts that provide lower continuation utility than their outside options; (ii) shareholders cannot commit to negative net present value (NPV) projects; (iii) both the managers and the shareholders cannot commit. We characterize the optimal contract under general convex adjustment cost functions and provide examples for which closed-form solutions can be obtained. We show that, as in the data, small firms invest more, grow faster, and have a higher Tobin׳s Q than large firms under the optimal contract. In addition, the pattern of the dependence of chief executive officer (CEO) compensation on past performance implied by our model is also consistent with empirical evidence.